Membangun Kerangka Konseptual Aspek Penguat Daya Saing Daerah (Studi Kasus di Kabupaten Jombang) - Rizka Mudyanti; Novi Trihutomo (Journal of Regional Economics Indonesia, 2022)
In the context of global competition, the level of competitiveness is one of the parameters used to realize sustainable development. The higher the regional competitiveness, the higher the level of community welfare. Regional competitiveness is the ability of the region to achieve sustainable quality development in order to achieve a high level of welfare while remaining open to domestic and international competition. However, efforts to strengthen regional competitiveness are, on average, difficult for the regions to carry out due to the relative lack of conceptual framework models in constructing indicators of regional competitiveness. Therefore, this study aims to construct indicators of regional competitiveness to create quality and sustainable development. Based on the qualitative method that was strengthened by FGD activities, this study found that there are four aspects that shape regional competitiveness, namely: (i) market aspects; (ii) HR aspects; (iii) aspects of the innovation ecosystem; and (iv) supporting aspects. Strengthening these four aspects based on their respective indicators can increase productivity, progress, competition, and regional independence. By measuring regional competitiveness and combining it with the advantages of local resources, it is hoped that the regional positioning can be known to improve development in the future. The results of this study can be used as a reference for local governments in making policies that are more targeted and encourage program synergies between sectors.